BUDAYA PENDIDIKAN AL-QUR’AN BAGI ANAK USIA DINI DI ERA TEKNOLOGI - Gesyani, Helma; Ritonga, Apri Wardana; Izzatul Arab; Indria Ningsih (Universitas Darunnajah, 2023)
The impact caused by technological developments has skyrocketed, especially among early childhood. Al-Qur'an is present as a fortress so as not to fall into negative things from this technological development. The purpose of this research is to formulate a new strategy in learning the Qur'an for early childhood in the era of technology. This research uses the library research method, namely research that utilizes library materials as a data source to answer the research problem formulation. Efforts to discuss that in the technological era there are many challenges in the context of learning the Qur'an, especially in early childhood. So the results of this study reveal that, among other things, firstly, Al-Qur'an education which is very relevant which is applied to early childhood in the midst of the development of the technological era. second, the Qur'anic education model is a model of learning the Qur'an in early childhood which has major implications for increasing children's intelligence. third, there are efforts we can make to increase children's love for reading and practicing the Qur'an in everyday life. So it is hoped that there will be further research to examine and test the effectiveness of learning the Qur'an for early childhood in the era of technological development, so that research uses a more comprehensive approach.